Genocide and resistance Nr. 5(1) - Valentukevičius, Rimvydas; Gauck, Joachim; Gaškaitė-Žemaitienė, Nijolė; Starkauskas, Juozas; Banionis, Juozas; Maslauskienė , Nijolė; Grigoraitis, Vidas; Kilikevičienė, Giedrė (Genocidas ir rezistencija, 1999)
Full Issue (paper copy scan)